Adaptation of The Use of Learning Technology for Mahasantri at The Kauman Pesantren in Lasem - Cholifah, Cholifah; Rubiyati, Dewi; Rohmawati, Isna; Ghozali, Ibnu Fikri (Jurnal Progress: Wahana Kreativitas dan Intelektualitas, 2024)
AbstractIslamic boarding schools face serious challenges in the digital era. The characteristic of Islamic boarding schools which uphold traditional values is that they have to deal with modern technological developments. Mahasantri Lack of access to technology because they think it interferes with their focus on learning. The aim of this research is to describe Mahasantri's adaptation in the use of technology, the obstacles faced, and the benefits obtained in the learning process with technology at the Kauman Lasem Islamic Boarding School. This type of research is descriptive qualitative. Data collection techniques were obtained from interviews with Kauman Lasem Islamic Boarding School caregivers, teachers and 4 Mahasantri, observations were made by observing and recording existing Mahasantri learning activities as well as policies on the use of technological tools permitted in Islamic boarding schools, documentation was obtained from official Islamic Boarding School documents. The research results show that the use of learning technology requires adaptation to the time for memorizing the Koran, the policy regarding limited use of technology has an impact on student Mahasantri who then have the initiative in carrying out assignments by not relying solely on laptop and gadget technology. The impact of this research is that Mahasantri have good time management skills. Adapting the use of technology in Islamic boarding schools as a learning support tool for Mahasantri, not replacing traditional values and Islamic teachings. Mahasantri have better digital skills to face challenges in the world of work in the digital era.